Data and code for "Strong plasmon-molecule coupling at the nanoscale revealed by first-principles modeling" - Rossi, Tuomas; Shegai, Timur; Erhart, Paul; Antosiewicz, Tomasz (Chalmers University of Technology, 2019)
The data includes atomic structures, time-dependent dipole moments, and photoabsorption spectra of the systems modeled and analyzed in the article "Strong plasmon-molecule coupling at the nanoscale revealed by first-principles modeling" by Tuomas P. Rossi, Timur Shegai, Paul Erhart, and Tomasz J. Antosiewicz.

The input scripts for reproducing the data are also included. The time-dependent density-functional theory calculations use the LCAOTDDFT module of the GPAW code, and the atomic structures are created with the ASE code.

See README.md in the archive for a detailed description.
Keywords: plasmon; strong coupling; time-dependent density-functional theory; Physical Sciences; Fysik